عہدعباسی عصراول میں علوم حدیث کاعلمی جائزہ: Intellectual Analysis of Hadith Disciplines in First Abbasid Period - Hayat Ullah; Dr. Noor Hayat Khan (MEI, 2023)
Hadith is the second source of legislation in Islam and its significance has been felt since the beginning up to its evolution. Moreover, the discipline acquired greater attention in the era of Companions (may God be pleased with them) which continued till the codification of Hadith. On one hand, Hadith has been shown interest from a number of perspectives such as: theological, legal and missionary and at the same time the discipline of Hadith saw its pinnacle. It started from oral transmission and small codices however, the foundations of this discipline were set during Umayyad rule which later on acquired a scholarly form in the prime time of Abbasid rule (132 AH to 247AH). During this golden era research went underway in different sub-disciplines – research into the textual content of Hadith, chains of transmission, biographies of narrators, Interpretation of rare and difficult terms and implicit weaknesses in Hadith among many. Hence, solid foundations of Hadith discipline were laid. This article brings forth the important Hadith scholars and their remarkable services in the era. It carries out an in-depth analysis of Hadith scholarship in the first part of the Abbasid rule. It contains discussion on the following topics: Introduction to Abbasid reign, family background and a brief discussion of its various time periods. Definition, types and importance of Hadith scholarship Publication of Hadith scholarship and services of renowned Hadith scholars during the pinnacle of Abbasid period. And introduction to the scholarly work in the field of Hadith during Abbasid era. An introduction to different disciplines of Hadith studies during Abbasid era.